0783 Compliance with Follow-up Polysomnogram in Patients Prescribed Oral Appliance Therapy for Treatment of Obstructive Sleep Apnea. (25th May 2022) - Kouassiaman, Courtland; Foster, Shannon; Powell, Tyler; Hansen, Shana; Brock, Matthew
Abstract: Introduction: Literature supports Oral Appliance Therapy (OAT) for mild-to-moderate obstructive sleep apnea (OSA) with evidence showing clinical benefits. The long-term ease of follow makes these devices attractive options for many though requires upfront provider and patient coordination. After prescription of OAT, a dental professional qualified in fabrication must evaluate the patient, the device must be fabricated and a follow-up polysomnogram (PSG) with the device in place should be obtained to determine treatment efficacy. If this guideline is followed in clinical practice is unknown with limited research. Our study evaluates the frequency of follow-up PSG in patients referred for OAT for treatment of OSA in a combined sleep and dental clinic. Methods: A retrospective chart review was performed to determine if OSA patients who elected to pursue OAT subsequently underwent a follow up PSG after obtaining their device. Patients who did not have their diagnostic study at our institution were excluded. Patients prescribed OAT for primary snoring were also excluded. Results: We identified 104 patients who were referred for OAT for treatment of OSA; 90 (86.5%) of which followed up with the dental clinic, 84 (80.8%) of which obtained devices, and 14 (13.5%) of which completed a PSG after obtaining their device. Additional review of the original 104 patients demonstrated: 88 (84.6%) were male, mean BMI was 27.6, mean AHI 15.1/hr, and mean age 38.9 years. Review of the 14 patients who obtained follow up PSGs with OAT showed: all were male, mean BMI 27.0, mean AHI 13.8/hr and mean age 38.6 years. Total sleep time (TST) in patients who had a follow up PSG with OAT (mean = 344.2 min) was significantly less than on their diagnostic PSG (mean = 367.2 min, p= 0.043). Conclusion: Although the AASM CPG for treatment of OSA with OAT recommends follow-up sleep testing to confirm efficacy, the follow-up PSG rate of 13.5% in a single-center closed system indicates poor patient adherence. Increased communication between the dental providers and sleep clinic is encouraged for proper follow up. Further research will need to be done to elucidate the individual and systemic barriers to appropriate follow-up. Support (If Any):